Perancangan Infrastruktur Kubernetes Untuk Aplikasi Data Center Infrastructure Management (Dcim) Studi Kasus Pt. Pelayaran Nasional Indonesia (Pelni) - Ayu Kinanti, Vinandita; Iqba, Muhammad; Mahendra Putra, Chandra (eProceedings of Applied Science, 2024)
In the digital era, PT Pelayaran NasionalIndonesia (PELNI) must strengthen itsIT infrastructure to manage data efficiently, safely,evaluating Kubernetes infrastructure based onmicroservices-based Kubernetes infrastructure for Data CenterInfrastructure Management (DCIM) application. The processincludes requirement identification, architecturearchitecture, Kubernetes cluster setup, and deployment of thedeployment of the application as a separate service.The results show that Kubernetes improvesoperational efficiency and data center availabilityPT.PELNI data center, while the microservices architecturearchitecture enables services that are more fault tolerant,scalable, and maintainable, as well as identifying technical challenges and opportunities.identified technical challenges and opportunitiesin its implementation. Keywords: kubernetes, dcim, microservices